Análisis de los Pactos de Borde de los cerros orientales de Bogotá D.C Frente al cumplimiento de los compromisos adquiridos por las entidades distritales y regionales. (2021)
The main goal degree project was to contribute to the follow up process to existing border pacts and which are found in making process in the urban-rural areas of the towns of de Usaquén, Chapinero, Santa Fe, San Cristóbal and Usme from eastern hills in Bogotá, with focus on neightborhoods located in the adequacy strip and in the Protective Forest Reserve "Bosque Oriental de Bogotá”. The initial identification of the structure of the border pacts was carried out considering their territorial problems and the commitments acquired by the district entities. Likewise, the analysis of the information collected through the different dialogue spaces was carried out, such as the Interlocution Committee of the eastern hills, the thematic dialogue tables, and the tours in the territory. Thanks to this was achieved, the systematization of the information regarding the progress of compliance with the commitments acquired within the framework of the competences of each entity, the generation of maps referring to the location and status of legalization and the participatory social mapping tool for the construction of the new border pact in the town of San Cristóbal.